2018
DOI: 10.1038/s41416-018-0142-6
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of androgen receptor and FOXA1 co-expression in non-metastatic triple negative breast cancer and correlation with other biomarkers

Abstract: AR + /FOXA1 + expression defines a luminal-like TNBC subgroup affected with a worse outcome compared to other TNBC and a higher risk of late recurrences. This subgroup appears enriched in PIK3CA mutations, suggesting a role for PI3K inhibitors in this subgroup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
70
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 11 publications
4
70
1
2
Order By: Relevance
“…In recent years, the relationship between the expression of FOXA1 and prognosis has been investigated in various cancers, including breast and prostate cancer . However, the influence of FOXA1 expression on prognosis differs according to the primary site.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In recent years, the relationship between the expression of FOXA1 and prognosis has been investigated in various cancers, including breast and prostate cancer . However, the influence of FOXA1 expression on prognosis differs according to the primary site.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the relationship between the expression of FOXA1 and prognosis has been investigated in various cancers, including breast and prostate cancer. [18][19][20][21][22][23][24][25][26][27][29][30][31][32][34][35][36][37] However, the influence of FOXA1 expression on prognosis differs according to the primary site. In SDC, we demonstrated that a high FOXA1 expression level was a good prognostic marker.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…J. Shou Наличие экспрессии РА и FOXA1 при ТНРМЖ определяет неблагоприятное течение заболевания, характеризующееся снижением БРВ и ОВ [92].…”
Section: обзорные статьиunclassified